2018
DOI: 10.2478/helm-2018-0029
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular changes and cortical neurodegenerative lesions in Trichinella spiralis infected BALB/c mice: a preliminary study elucidating a potential relationship between systemic helminthic infections and idiopathic Parkinson’s

Abstract: SummaryIdiopathic Parkinson’s (IP) is a neurodegenerative disease that is suspected to be due to exposure to infections during early life. Toxoplasmosishas been the only suspected parasitic infection in IP (Celik et al., 2010). Recently, some non-central nervous system bacterial and viral infections have been incriminated in IP (Çamcı & Oğuz, 2016). So in the current study, we tried to explore if the systemic inflammatory reactions triggered by some helminths like Trichinella spiralis can induce Parkinsonian l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 88 publications
1
9
0
Order By: Relevance
“…Trichinellosis is a serious foodborne parasitic zoonosis caused by the nematode of the genus Trichinella, which is characterized by an extremely wide host range and worldwide distribution (Brus chi,2012;Goździket al, 2017). The pathology of trichinellosis is associatedwithinitialinfl ammatoryresponseduringtheintestinal phase,andsubsequentallergicandinfl ammatoryresponsesduring larval migration and invasion of the host muscles (Bruschi & Chiumiento, 2011;Hasby Saad et al,2018).Theeffi cacyofclassic therapy with benzimidazoles is limited due to weak activity against encapsulated larvae, low water solubility, anthelmintic resistance, contraindication in children and pregnancy (Yadav & Temjenmong la, 2012). The antiparasitic potential of alternative therapeutic approaches is therefore increasing in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Trichinellosis is a serious foodborne parasitic zoonosis caused by the nematode of the genus Trichinella, which is characterized by an extremely wide host range and worldwide distribution (Brus chi,2012;Goździket al, 2017). The pathology of trichinellosis is associatedwithinitialinfl ammatoryresponseduringtheintestinal phase,andsubsequentallergicandinfl ammatoryresponsesduring larval migration and invasion of the host muscles (Bruschi & Chiumiento, 2011;Hasby Saad et al,2018).Theeffi cacyofclassic therapy with benzimidazoles is limited due to weak activity against encapsulated larvae, low water solubility, anthelmintic resistance, contraindication in children and pregnancy (Yadav & Temjenmong la, 2012). The antiparasitic potential of alternative therapeutic approaches is therefore increasing in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Trichinella spiralis NBL migration is considered the most dangerous phase of infection, during which there is a generalized extensive immune-inflammatory reaction resulting from the high antigenicity of the larvae (Pozio, 2007). They can cause systemic inflammatory manifestations all over the body before habituating their final destination (Saad et al, 2018). The lung is one of the main organs for the retention and destruction of NBL (Bruschi et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Farid et al (2019) observed acute hepatitis in response to infection with T. spiralis in rats. Saad et al (2018) reported that trichinellosis caused a cerebrovascular disease in 10-20% of patients. Moreover, cardiac and cerebral affections are the most fatal complications in this phase (Pozio et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations